PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI PADA DINAS KOPERASI, USAHA MIKRO KECIL, USAHA MENENGAH DAN PERINDUSTRIAN KOTA METRO - H Muh Amir; Dita Waskatita (Universitas Bandar Lampung (UBL), 2020)
Problems faced by The Office of Cooperatives, UMK, UM and Industry in Metro City are the lack of attention of leaders to subordinates and leaders less actively involving employees in office matters. The application of a culture of honesty, perseverance and discipline in the Department of Cooperatives, UMK, UM and Industry in Metro City is still not effective. Both elements of these variables have an impact on the non-optimal performance of employees that can be seen from the results of work that is not in accordance with organizational goals. Based on these issues then the problem is: (1) How does the influence of leadership style on staff performance? (2) How does the influence of organizational culture on staff performance? (3) How does the influence of leadership style and organizational culture together on staff performance?. The purpose of this research is to find out, analyze and explain the influence of leadership style and organizational culture on staff performance at the Office of Cooperatives, UMK, UM and Industry Metro City both partially and simultaneously. Use traditional research is descriptive method with type of library research and field research and data collection technique used observation, questionnaires and documentation. Sources of data derived from primary and secondary data. This study uses quantitative analysis method by means of product moment correlation analysis and multiple regression. The test results for the relationship between leadership style on satff performance obtained t count of 3.621. Furthermore, for organizational culture variables on employee performance, it is obtained t count 3.665. Testing simultaneously or together obtained statistical F results of 27.850. It was concluded that this study found a significant influence both partially and simultaneously between Leadership Style and Organizational Culture on Employee Performance at the Office of Cooperatives, UMK, UM and Industry in Metro City.